Parola di Dio - Parola del Signore: un'applicazione della teoria narrativa alla proclamazione liturgica della Scrittura - Invernizzi, Laura (Teologia, 2025)
This paper explores the liturgical proclamation of Scripture as a form of quotation, analysing how biblical texts, when inserted into the ritual context of the liturgy, acquire a renewed meaning distinct from their original setting. Drawing on Meir Sternberg's narrative theory and contemporary liturgical hermeneutics, the study argues that the liturgy does not merely read Scripture but re-presents it as a living, present, and performative word. The essay offers a theoretical reflection on the phenomenon of quotation and illustrates its liturgical implications through a case study: the first reading of the Christmas Midnight Mass (Isaiah 9:1-6). The analysis highlights the dynamic tension between source and frame, between original meaning and liturgical interpretation, providing tools for a deeper understanding of the Word of God in the act of celebration.